Genetic Determination of Coagulation Factor VIIc Levels among Healthy Middle-aged Women - Meilahn, Elaine; Ferrell, Robert; Kiss, Joseph; Temple, Anne; Green, Fiona; Humphries, Steve; Kuller, Lewis (Thrombosis and Haemostasis, 1995)
A recent study (1) reported variation among men in clotting factor Vile levels is associated with a genetic polymorphism detected by the restriction enzyme Msp I. The present study determined the Msp I genotype (Arg353, Gln353 alleles) for 189 women (mean age 53) who were subjects in the Healthy Women Study, a population study of CHD risk factor change at menopause. Women with the Arg/Arg genotype (n = 147) had an 16% higher (geometric) mean FVIIc level than those with the Arg/Gln (n = 41) genotype (1.21 vs 1.04 U/ml, p<0.01), while the one subject with the Gln/Gln genotype had an FVIIc level of 1.00 U/ml. These results are consistent with those previously found in healthy men (1). In addition, women carrying the Gin allele did not exhibit the elevation in FVIIc with menopause and use of hormone therapy found among those with the Arg allele, suggesting that genotype may modify the observed rise in factor Vile at menopause. Possibly because of the small sample size this interaction did not reach conventional levels of statistical significance. Results of multiple linear regression analyses controlling for age, hormone use, obesity, (In) triglyceride levels, and family history of CHD found FVIIc levels to be significantly (p<0.001) related to genotype. Thus, genotype appears to be a major determinant of FVIIc levels among women.